A NEW SPECIES AND SYNOPSIS OF ADELOCARYUM (BORAGINACEAE – CYNOGLOSSEAE) WITH NOTES ON LINDELOFIA AND BRANDELLA - Mill, R. R. (Edinburgh Journal of Botany, 2010)
Adelocaryum Brand (Boraginaceae – Cynoglosseae) is shown to be the correct name for Paracaryopsis (H.Riedl) R.R.Mill, and the new combination Adelocaryum lambertianum (C.B.Clarke) R.R.Mill is made. The new species Adelocaryum nebulicola R.R.Mill is described from Oman and its affinities with the Indian species A. coelestinum (Lindl.) R.R.Mill are discussed. A synopsis of and revised key to the entire genus is provided as well as a revised description of Adelocaryum coelestinum. As circumscribed here Adelocaryum is restricted to tall mesophytic herbs lacking long glochidiate spinules on the wing-like margin of the nutlets. The desert annual or biennial Brandella erythraea is here excluded from Adelocaryum. The new combination Brandella erythraea forma subexalata (H.Riedl) R.R.Mill is made. Lindelofia spectabilis Lehm., for which the current correct name is L. longiflora (Benth.) Baill., is designated lectotype of the genus Lindelofia Lehm.
Keywords: Adelocaryum; Boraginaceae; Brandella; disjunction; India; lectotypifications; Lindelofia; new combination; new species; Oman; Paracaryopsis